S-ICD Implantation "Tips and Tricks" - Szymon Budrejko; Maciej Kempa; Andrzej Przybylski (Reviews in Cardiovascular Medicine, 2023)
An implantable cardioverter-defibrillator (ICD) was developed to provide protection against sudden cardiac death. Despite being effective in terminating ventricular arrhythmias, traditional transvenous ICDs appeared over time to have certain limitations related to the need for vascular access and the presence of foreign material inside the circulatory system (namely lead failure and infections). A subcutaneous implantable cardioverter-defibrillator (S-ICD) was developed to overcome those limitations and to provide prevention against sudden cardiac death from outside the cardiovascular system. Utilization of that modern method of treatment is constantly increasing worldwide, and new centers incorporate implantation of that system in their portfolio. This review aims to present the most relevant issues related to S-ICD implantation procedure, based on experience of the authors and an extensive literature search.